The structure of the elicitor Cerato-platanin (CP), the first member of the CP fungal protein family, reveals a double ψβ-barrel fold and carbohydrate binding - de Oliveira, Aline L. (2011)
Cerato-platanin (CP) is a secretion protein produced by the fungal pathogen Ceratocystis platani, the causal agent of the plane canker disease and the first member of the CP family. CP is considered a pathogen-associated molecular pattern because it induces various defense responses in the host, including production of phytoalexins and cell death. Although much is known about the properties of CP and related proteins as elicitors of plant defense mechanisms, its biochemical activity and host target(s) remain elusive. Here, we present the three-dimensional structure of CP. The protein, which exhibits a remarkable pH and thermal stability, has a double ψβ-barrel fold quite similar to those found in expansins, endoglucanases, and the plant defense protein barwin. Interestingly, although CP lacks lytic activity against a variety of carbohydrates, it binds oligosaccharides. We identified the CP region responsible for binding as a shallow surface located at one side of the β-barrel. Chemical shift perturbation of the protein amide protons, induced by oligo-N-acetylglucosamines of various size, showed that all the residues involved in oligosaccharide binding are conserved among the members of the CP family. Overall, the results suggest that CP might be involved in polysaccharide recognition and that the double ψβ-barrel fold is widespread in distantly related organisms, where it is often involved in host-microbe interactions.